Study of hemodynamic and airway reflexes during emergence from general anaesthesia and tracheal extubation with and without using dexmedetomidine in patients undergoing laparoscopic cholecystectomy - KC, Gaurav; Amatya, Bishwo Ram; Bista, Sachhyatkar (Journal of Patan Academy of Health Sciences, 2024)
Introduction: The emergence phase and tracheal extubation are critical due to potential hemodynamic changes and airway reflexes. This study aimed to evaluate the effectiveness of Dexmedetomidine in mitigating these responses during extubation.Method: Forty-eight American Society of Anesthesiologists physical status (ASA-PS) I and II patients, aged 18-60 years , undergoing elective laparoscopic cholecystectomy were enrolled at Shree Birendra Hospital, Kathmandu after Institutional Review Committee approval. Group D received 0.25 mcg/kg Dexmedetomidine in 100 ml saline, while Group N received 100 ml saline over 10 minutes at the end of surgery. Heart rate and Mean Arterial Pressure (MAP) were recorded at different time intervals. Extubation smoothness was rated on a 5-point scale. Statistical analysis used Fisher’s exact test/chi-square test for categorical variables and Mann-Whitney test or independent t-test for continuous variables. Repeated measures were assessed with RM ANOVA. A p-value of